Impact of slope gradient on tree biomass, carbon sequestration, and ecological functions in Rayagada District, Odisha, India - Mishra, Prasanta Kumar; Kaushal, Rajesh; Islam, Sadikul; Ramajayam, D.; Kumar Samal, Saubhagya; Jena, Kulaswami Jagannath; Lenka, Pravu Charan; Tomar, J. M. S.; Madhu, M. (Frontiers in Agronomy, 2025)
The Eastern Ghats of Odisha are ecologically fragile, facing land degradation, soil erosion, and livelihood insecurity. This study evaluates the carbon sequestration potential of 12 multipurpose tree species planted across slope gradients (upper, middle, and bottom) in 3 eco-villages of Rayagada district using a 1-acre family farm model. Results after 9 years revealed significant variations in the 1-acre farm model, with bottom slopes exhibiting the highest tree density (82 trees), average height (4.27 m), crown spread (4.5 m), and carbon sequestration (73.1 Mg CO2). Among species, A. occidentale and M. indica contributed the highest carbon stocks (7.27 and 6.97 Mg) and sequestration potential (26.70 and 25.59 Mg CO2, respectively), while S. glauca and C. siamea showed superior biomass (631.6 and 627.1 kg tree−1) after 9 years of plantation. The integrated 1-acre family farm model system produced carbon stock of 42.1 Mg acre−1, sequestered a total of 154.5 Mg CO2 acre−1, released 112.4 Mg oxygen acre−1, and generated carbon credits worth Indian Rupee (INR) 256437. Tree-based systems improved soil organic carbon and reduced bulk density and sustained crop yields and farm income (₹1.1–1.13 lakh per farmer) after 9 years of plantation. Overall, the findings demonstrate that slope-specific tree planting enhances ecological restoration, carbon sequestration, and livelihood resilience and provide a basis for eco-village–based agroforestry models to advance climate-smart development in the Eastern Ghats.